Solving the traffic and flitter challenges with tulip - Simonetto, P.; Koenig, P.-Y.; Zaidi, F.; Archambault, D.; Gilbert, F.; Trung-Tien Phan-Quang; Mathiaut, M.; Lambert, A.; Dubois, J.; Sicre, R.; Brulin, M.; Vieux, R.; et al. (2009 IEEE Symposium on Visual Analytics Science and Technology, 2009)
We present our visualization systems and findings for the badge and network traffic as well as the social network and geospatial challenges of the 2009 VAST contest. The summary starts by presenting an overview of our time series encoding of badge information and network traffic. Our findings suggest that employee 30 may be of interest. In the second part of the paper, we describe our system for finding subgraphs in the social network subject to degree constraints. Subsequently, we present our most likely candidate network which is similar to scenario B.